From the Damascus covenant to the covenant of the community : literary, historical, and theological studies in the Dead Sea scrolls - Hultgren, Stephen, 1971- (Studies on the texts of the Desert of Judah, 2007)
The focus of this volume is a history of covenantal theology in the Dead Sea Scrolls. At the heart of the work the author provides new insight into the origins of the \'new covenant in the land of Damascus\' (\'Damascus covenant\') and of the Qumran community (\'covenant of the community\'). The \'Damascus covenant\' arose as a national restoration movement in Third century BC Palestine among Jews who traced their history back to the returnees from exile. The Qumran community emerged out of the Damascus covenant in the 2nd century BC as a refuge for the faithful when the Damascus covenant and the Teacher of Righteousness suffered the betrayal of some of their adherents. Other chapters explore the topics of dualism, the righteousness of God in the thanksgiving hymns, and covenant renewal.